2019
DOI: 10.1186/s13104-019-4523-6
|View full text |Cite
|
Sign up to set email alerts
|

Heart disease in pregnancy—clinical pattern and prevalence: initial data from the first cardio-maternal unit in Iraq

Abstract: Objectives The purpose of this study to determine the clinical pattern and prevalence of heart disease in pregnancy at the first established cardio-maternal unit in Iraq over the last 4 years; since January 2015 till May 2019. Data are presented as number and percentage. Results A total of 252 pregnant women presented to cardio-maternal unit included in this study. According to the collected data, among the main diagnosis of heart disease during pregnancy was valvular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Farhan et al did a study for heart disease in pregnancyclinical pattern and prevalence at a cardio-maternal unit at Iraq in 2019 and found that from 252 patients with heart disease 34.1% was valvular disease, followed by congenital heart disease in 30.5%, cardiomyopathy in 29.8%, pulmonary hypertension in 4% and ischemic heart disease in 1.6%. 2 Shrestha et al did a systemic review and meta-analysis of prevalence and outcome for pregnancy with heart disease in South Asia, included 25 studies in final quantitative synthesis and found the result that prevalence of heart disease in pregnancy was 1.46%. From that 70.25% had rheumatic heart disease and 18.1% had congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Farhan et al did a study for heart disease in pregnancyclinical pattern and prevalence at a cardio-maternal unit at Iraq in 2019 and found that from 252 patients with heart disease 34.1% was valvular disease, followed by congenital heart disease in 30.5%, cardiomyopathy in 29.8%, pulmonary hypertension in 4% and ischemic heart disease in 1.6%. 2 Shrestha et al did a systemic review and meta-analysis of prevalence and outcome for pregnancy with heart disease in South Asia, included 25 studies in final quantitative synthesis and found the result that prevalence of heart disease in pregnancy was 1.46%. From that 70.25% had rheumatic heart disease and 18.1% had congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is the need of the hour for medical professionals to act as a multidisciplinary team including gynecologist, anesthetist, physician, cardiologist, and neonatologist for improving the fetomaternal outcome of these patients. [2][3][4][5][6] The present retrospective analysis is an attempt to assess the impact of cardiac diseases on pregnancy and understanding their indifferent presentations for the better alignment and understanding of cardiac diseases in pregnancy so that right step can be taken at the right time to improve maternal and fetal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…But after 2010, the rate of maternal mortality began to decline, despite increase in the number of high risk patients. This decline is attributed to improvement in medical service [4]. This means that with proper preventive measures, these diseases can be detected early and the progress of the disease can be altered.…”
Section: Introductionmentioning
confidence: 99%